What Attributes Matter Most in Physicians? Exploratory Findings from a Single-Centre Survey of Stakeholder Priorities in Cancer Care at a Canadian Academic Cancer Centre - Deepro Chowdhury; Katie Laurie; Tinghua Zhang; Dominick Bossé; Paul Wheatley-Price (Current Oncology, 2023)
Background: Limited research exists regarding how healthcare stakeholders prioritize the importance of differing physician attributes in oncologists. Identifying these priorities can help ensure that Canadian cancer care continues to meet the needs of its patients. In our previous research, compassion and empathy were identified as important physician attributes, with answers like knowledge, professionalism or communication less common. We hypothesized that respondents may have been assuming other, underlying qualities in their oncologists when they prioritized “compassion” and “empathy”. To test this, the current study asks respondents to rank important physician attributes. Methods: With ethics approval, we asked healthcare stakeholders (physicians, nurses, patients, caregivers, medical students, and allied healthcare providers) to rank the eight most popular qualities or attributes. We identified differences between which characteristics each group valued most in physicians. Results: 375 respondents participated in the survey. “Knowledge” and “competence” were the most popular answers in the current study among all groups except medical students. Conclusion: Previously, we identified compassion as a highly valued attribute; however, this survey suggests that this may be with the assumption that a physician is knowledgeable and competent. Future research will use semi-structured interviews to investigate respondents’ rationales for making their choices and help interpret our findings in this study.